Efecto de la neuroeducación física en las funciones cognitivas en estudiantes de cuarto grado de primaria en la Institución Educativa República de Venezuela del distrito de Iquitos 2024 - Suero Pinedo, Freddy Junior (2025)
Physical education for children in the fourth cycle of primary school has changed, particularly with the contributions of neuroscience to the brain. The effect of the physical neuroeducation program on cognitive functions was evaluated in fourth-grade students at the República de Venezuela 2024 Elementary School. The research was quasi-experimental, using an educational program to find solutions to practical problems. The research was quantitative, with an experimental and control group. Pre- and post-test questionnaires were used, and statistical tests were systematized and applied. The sample consisted of 139 students, divided into an experimental group to whom the program was applied, and a control group without the program. It is concluded that the physical neuroeducation program had a favorable effect on cognitive functions (physical health in attention, mental health in memory, social health in motivation, inner health in emotion, and emotional health in motivation). In summary, the effectiveness of the neuroeducational approach is evident in promoting integrated physical and cognitive development in students.